On Certain Class of Bazilevič Functions Associated with the Lemniscate of Bernoulli - Tamer M. Seoudy; Amnah E. Shammaky (Journal of Function Spaces)
Making use of the principle of subordination, we introduce a certain class of multivalently Bazilevic˘ functions involving the Lemniscate of Bernoulli. Also, we obtain subordination properties, inclusion relationship, convolution result, coefficients estimate, and Fekete–Szegö problem for this class.